The Wilson loop — large spin OPE dictionary - Bercini, Carlos [UNESP]; Gonçalves, Vasco [UNESP]; Homrich, Alexandre [UNESP]; Vieira, Pedro [UNESP] (Springer Nature, 2022)
We work out the map between null polygonal hexagonal Wilson loops and spinning three point functions in large N conformal gauge theories by mapping the variables describing the two different physical quantities and by working out the precise normalization factors entering this duality. By fixing all the kinematics we open the ground for a precise study of the dynamics underlying these dualities — most notably through integrability in the case of planar maximally supersymmetric Yang-Mills theory.
Keywords: AdS-CFT Correspondence; Scale and Conformal Symmetries; Supersymmetric Gauge Theory; Wilson, ’t Hooft and Polyakov loops